2020
DOI: 10.1177/0739986320915649
|View full text |Cite
|
Sign up to set email alerts
|

Testing Traditional Machismo and the Gender Role Strain Theory With Mexican Migrant Farmworkers

Abstract: The current study examines the moderating role of traditional machismo on mental health outcomes. We hypothesized that machismo would enhance the effects of stressors that are incongruent with traditional machismo beliefs (discrimination, adverse childhood experiences [ACEs], and fear of deportation) on depression and anxiety outcomes but would not enhance stressors that are congruent (harsh working conditions and poverty) on depression and anxiety. Participants were 190 male Mexican migrant farmworkers. As hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This review has highlighted the role of identities in WRI experiences for migrant women workers, including both gender and migrant identities, and the intertwining of these. Previous research has explored the role of gendered identities such as “machismo” in workplace exploitation ( 119 ) and WRIs for migrant men ( 120 ), however, further investigation is needed to determine the extent to which gender identities shape women migrants' WRI outcomes and experiences.…”
Section: Discussionmentioning
confidence: 99%
“…This review has highlighted the role of identities in WRI experiences for migrant women workers, including both gender and migrant identities, and the intertwining of these. Previous research has explored the role of gendered identities such as “machismo” in workplace exploitation ( 119 ) and WRIs for migrant men ( 120 ), however, further investigation is needed to determine the extent to which gender identities shape women migrants' WRI outcomes and experiences.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional male gender role in the Latinx culture, also known as machismo, impacts how Latinx men act and interact with others (Nuñez et al, 2016). Having more machismo was related to a stronger impact of discrimination on depressive symptoms (Acosta et al, 2020). The cultural gender roles, specifically machismo, may put Latinx males in a more vulnerable state to be more influenced or hurt by accusations of assimilation from family members.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, examining the potential mechanism that adherence to gender roles has on the association between postimmigration stress and depressive symptoms may explain potential differences in outcomes in this population. Prior work among Latinx populations has demonstrated that adherence to gender roles increases the effect of stressors on depressive outcomes (Acosta et al., 2020). Components of Latinx gender roles may cause negative cognitive emotional regulatory practices during the process of coping with stress and depressive symptoms (Nuñez et al., 2016).…”
Section: Discussionmentioning
confidence: 99%